Climate change and asian agriculture - Rosegrant, Mark W.; Yohe, Gary; Ewing, Mandy; Valmonte-Santos, Rowena; Zhu, Tingju; Burton, Ian; Huq, Saleemul (2010)
Asian and global agriculture will be under significant pressure to meet the demands of rising populations, using finite and often degraded soil and water resources that are predicted to be further stressed by the impacts of climate change. In addition, agriculture and land use change are prominent sources of global greenhouse gas (GHG) emissions. The application of fertilizer, rearing of livestock, and land management lead to high levels of GHG in the atmosphere and significant amount of carbon storage and consequently, substantial sequestration potential. While impending climatic changes will have negative effects on agricultural production in parts of Asia, and especially on resource-poor farmers, the sector also presents opportunities for emission reductions. Warming across the Asian continent will be unevenly distributed, but will certainly lead to crop yield losses in much of the region and subsequent impacts on prices, trade, and food security--disproportionately affecting poor people. Most projections indicate that agriculture in South, Central, and West Asia will be hardest hit.
This paper discusses two approaches to responding to the impacts of climate change: mitigation and adaption. Mitigation--or the reduction GHG emissions--is essential to slow down climate change. The primary opportunities for pro-poor mitigation in the agricultural sector in Asia involve soil carbon sequestration, rice cultivation, and grazing land management. China and India, the world's largest producers of rice, also emit the vast majority of global methane emissions from rice. Potentials exist for low- and no-cost mitigation policies in this sector but significant reforms in the international climate policy framework and in the implementation of carbon mitigation are needed to reduce transactions costs and increase the incentives for small farmer participation.
In addition, as climate change has already begun, adaption--or the modification of agricultural practices and production--will be imperative if the growing food demands of modern society are to be met. However, many developing countries exhibit a lack of sufficient adaptive capacity. As a result, there is a potential critical role for national governments, nongovernment organizations, and international institutions in building the necessary adaptive capacity and risk management structures. Mitigation and adaption must be pursued in tandem. The greater the level of mitigation that can be achieved at affordable cost, the smaller the burdens placed on adaptation.
Keywords: Climate change mitigation; Greenhouse gas mitigation; Agriculture; Climate change